Meningkatkan kemampuan komunikasi matematis siswa SMP PGRI 1 Cimahi kelas VIII melalui pendekatan realistic mathematics education (RME) - Sarah, Siti; Sabandar, Jozua; Novtiar, Chandra (IKIP Siliwangi, 2024)
The aim of this research is to examine the influence of the Realistic Mathematics Education (RME) approach in improving students' mathematical communication ability. In this research, a quasi-experiment was used, with the research using the non-equivalent pretest-posttest control group design. Eighth grade students at PGRI 1 Cimahi Middle School were the subjects of the research. To measure mathematical communication ability, data was obtained from four test questions that had been tested previously. Next, the data obtained will be analyzed and processed using analysis of 2 dependent samples using a normality test first, followed by a paired t-test. Mathematical communication ability improve much better for students who use the RME Approach compared to students who use the regular learning approach.